Leadership Styles for Foreign Operations - Carlisle, Arthur Elliott (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The author discusses on the criteria to follow in choosing a style of leadership which is to be applied to foreign operations. In a country which is colonial in tradition, the authoritarian job-centered approach may be preferable. On the long run nonetheless, an organization wishing to be accepted in a foreign country can benefit enormously by using a democratic people-centered style in managerial decision making.